ROLE OF MANAGEMENT ACCOUNTING IN THE ACTIVITIES OF LOGISTICS ORGANIZATIONS - E. Yu. Knyazeva (Publishing House of the State University of Management, 2020)
The role of management accounting in the activities of logistics organizations has been considered. Some approaches to understanding the logistics system, explained by the multidimensional nature of this concept, have been adduced. The elements of the logistics system, which, depending on the location in the system, perform certain functions, have been highlighted. The interaction of factors contributing to the achievement of competitive advantages of the logistics system has been substantiated. The main goal of management accounting – to provide managers with the data they need to make timely management decisions has been revealed. The main tasks, that are solved using the management accounting system, have been enumerated. It has been concluded that a well-structured management accounting should take into account all cash flows (cash and non-cash), allowing you to visually assess the profitability of the business as a whole, as well as each project separately.